2018
DOI: 10.3389/fphar.2018.01130
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Altered the Metabolism of Loureirin B and the Expression of Major Cytochrome P450 in Liver of Rats

Abstract: Loureirin B (LB) is the marker compound of dragon blood (DB), which exhibits great potentials in protecting astronauts’ health against radiation and simulated microgravity (SM). Pharmacokinetics of LB is reported to be significantly altered by SM. Here, we investigated key metabolic features of LB in rat liver microsome (RLM) and the effects of SM on LB metabolism as well as on expression of major hepatic cytochrome P450 (CYP450) isoforms. Ten metabolites were tentatively identified based on fragmentation path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A recent study showed that microgravity induced lipid dysregulation in the mouse liver [ 20 ], and SMG similarly affected rat liver function by altering the metabolism of loureirin B and the expression of major cytochrome P450 [ 21 ]. The liver is one of the largest organs in the human body and plays an important role in the metabolism of carbohydrates, proteins, and lipids [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that microgravity induced lipid dysregulation in the mouse liver [ 20 ], and SMG similarly affected rat liver function by altering the metabolism of loureirin B and the expression of major cytochrome P450 [ 21 ]. The liver is one of the largest organs in the human body and plays an important role in the metabolism of carbohydrates, proteins, and lipids [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds showed decreased absorption, slower elimination, and double peaks in concentration–time curves in SMG rats. Metabolism of LB in the SMG rat liver microsome; LA, LC, DHF in the human liver microsome, and altered expression of drug-metabolizing enzymes in liver and intestine of SMG rats have been reported in our previous studies [ 58 , 59 , 60 ]. Altered drug-metabolizing enzymes and PK behaviors of DB compounds may be related to the therapeutic effects of DB in SMG rats.…”
Section: Discussionmentioning
confidence: 66%
“…Studies have shown [42][43][44] that microgravity changes metabolites in the body, and therefore we examined the metabolomics of the SB and MC groups. Serum specimens were subjected to untargeted metabolomics analysis to identify the hematic metabolic pro les among the two groups tested (Fig.…”
Section: Metabolic Patterns In the Sb Group And The MC Groupmentioning
confidence: 99%